A few remarks on the interpretation of European company law - Napierała, Jacek (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
The application of European company law by domestic courts entails prior interpretation of EU legislation. Firstly, the manner of interpretation of European company law is affected by both the specific nature of European company law and l’acquis communautaire. Secondly, interpretation methods are subject to the principle of uniform interpretation, which aims to safeguard uniform understanding and application of l’acquis EUwide. Thirdly, when undertaking pro-European interpretation one must (i) have regard to all domestic methods of interpretation, (ii) in line with the blanket ban on contra legem interpretation, and (iii) bear in mind the purpose and wording of a directive serving as a point of reference for pro-European interpretation, as far as possible.